Clinical Application of Pariksa: An Ayurvedic Perspective of Examination - Sharma, Durgesh Nandini; Yadav, Chhaju Ram; Sharma, Brahm Dutt (International Research Journal of Ayurveda & Yoga, 2022)
An attempt has been made to explain the clinical significance of Parīkṣā for fulfillment of the aim of Ayurveda, both in prevention and cure as well as in field of research. Various Ayurvedic classics and research article related to Parīkṣā were collected and analyzed. Contemporary and recent research article regarding clinical examination were searched online from google scholar, PubMed, Medline Plus etc. Ayurvedic classics were searched for better understanding of concept. Examination of patient and disease is very important in clinical practice, as it forms basis for treatment. Concept of Dashavidha pareeksha described in Ayurveda is very much scientific in terms of understanding the span of life and strength of person with probable cause and strength of the disease.